A Rejoinder To J. Glen Taylor - Wiggins, Steve A. (1997)
An on-going debate in which Wiggins replies to Taylor's criticisms of his work as voiced in 'A Response to Steve A. Wiggins, "Yahweh: The God of Sun?"', JSOT 71 (1996), pp. 107-19. Three areas are dealt with here: (1) the use of evidence, (2) the issue of metaphor, and (3) the significance of iconography.